2018
DOI: 10.1111/pace.13409
|View full text |Cite
|
Sign up to set email alerts
|

Physiological pacing in young patients with complex congenital heart defects

Abstract: In young CHD patients, endocardial/epicardial CLS-atrial pacing demonstrated a physiological response of heart rate to neurovegetative and physical stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In SND, atrial pacing is better than ventricular pacing. Rate-responsive sensors will produce more physiologic stimulation [27,28]. In the PACES Statement, atrial or dualchamber PM is recommended.…”
Section: Sinus Node Dysfunction (Snd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In SND, atrial pacing is better than ventricular pacing. Rate-responsive sensors will produce more physiologic stimulation [27,28]. In the PACES Statement, atrial or dualchamber PM is recommended.…”
Section: Sinus Node Dysfunction (Snd)mentioning
confidence: 99%
“…Class II a recommendations refer to antitachycardia pacing in CHD patients with recurrent intra-atrial reentrant tachycardia in whom ablation or medications were ineffective or not acceptable treatment [36,37]; atrial or dual-chamber pacing in patients with complex CHD and with impaired hemodynamic caused by sinus bradycardia or loss of AV synchrony as in single-ventricle physiology [28,38]. Class II recommendations apply to patients with SND, CHD and mean awake resting HR < 40 bpm and/or prolonged pauses: COR II a in the presence of a complex CHD; COR II b in the presence of a moderate CHD [23].…”
Section: Chdmentioning
confidence: 99%
“…Careful programming of pacemaker systems in regard of timing intervals is crucial as many pitfalls may arise (eg, Pacemaker mediated tachycardia, impaired ventricular function, and left ventricular filling, 2:1 block response). Recently Silvetti et al 6 have shown that atrial CLS pacing using transvenous as well as epicardial leads is effective in young patients with operated complex congenital heart defects (CHD). Atrial CLS pacing should be considered an alternative.…”
Section: Commentarymentioning
confidence: 99%